Managing extremes in the Anthropocene: a causal, stochastic physics approach - Kaluarachchi, Samadhee; Alila, Younes (Frontiers in Environmental Science, 2025)
Anthropogenic activities have led to an alarming rise in frequencies and severities of hydroclimatic extremes, resulting in deaths, adverse health impacts, near-destruction of municipalities, and trillions of US dollars or equivalent in economic impacts worldwide. With trends expected to continue or intensify, there is growing pressure to re-evaluate current adaptation and mitigation strategies. Here, it is demonstrated that while much of risk management, particularly of floods, remains magnitude-centric, a frequency-centric approach is key for reliably predicting risks and designing cost-effective solutions. This approach requires bridging hydroclimatology’s extreme value theory with the modern science of causation through stochastic physics. It anchors physical understanding in probabilistic frameworks, centring environmental and anthropogenic controls when modelling and interpreting frequency distributions. Linking natural controls to a system’s undisturbed state and subsequent frequency-centric quantification of anthropogenic influence highlights large frequency changes far surpassing changes in magnitude, aligning scientific and professional practice with reality. In fact, the dramatic rise in extremes likely arises in part as a manifestation of an undisturbed distribution that is inherently highly sensitive to anthropogenic change, a crucial question for risk management. Only with an accurate portrayal of risk and sensitivity grounded in the deeper meaning of probability can hydroclimatology motivate strong policies and support the design of innovative solutions in the Anthropocene.